A Comparative Study of Novice and Experienced English Teachers’ Reinforcement Strategies in Rural and Urban English Classrooms - Ni Made Wita Anggarawati; Iga Lokita Purnamika; Ni Luh Putu Eka Sulistia Dewi (International Journal of Community Engagement Payungi, 2025)
The current study focused on comparing the reinforcement strategies used by novice English teachers and experienced English teachers in rural and urban areas. The challenges in implementing the reinforcement strategies were also obtained in this study. The study used qualitative approach as the research design. The data were collected from observation and interview. The research instruments were observation sheet, and interview guide. The data were analyzed by using THEMATIC analysis consisted of several steps; familiarizing data, generating initial codes, searching for themes, reviewing potential themes, defining and naming themes, producing report. After analyzing the data, method triangulation was conducted to ensure the data credibility. The findings were; The novice English teachers conducted similar reinforcement strategies in rural and urban context. The verbal form was often in the simple praise to engage and motivate students meanwhile the non-verbal forms; gesture, proximity, contact, and symbol were used as the corrective or reflective manner on students’ works. The experienced English teachers also conducted positive and negative reinforcement strategies both in rural and urban areas manifested in verbal and non-verbal forms, but they frequently used verbal forms; such as praise but more contextual and academic. The novice English teachers encountered several challenges in applying the reinforcement in rural and urban areas. There were six challenges faced by the teachers, such as; misinterpretation of reinforcement, student disengagement, student diversity, avoidance of competitive reinforcement, need individualized reinforcement strategies, inconsistent application of reinforcement.